(untitled) (Revista Venezolana de Salud Pública, 2019)
The prevalence of protozoa in the oral cavity, of 100 indigenous patients from Isla Ratón, Amazonas State, Venezuela (53 men and 47 women) with ages between 18 and 68 years was determined. The study was based on the analysis of samples of dental tartar and saliva, which were introduced into microcentrifuge tubes, to be transferred to the Bioanalysis Laboratory, from which aliquots (three times per sample) were taken with the help of a wood shaker to place them on a slide, which previously contained a drop of isotonic saline solution and a drop of lugol dye (direct examination), both lamellae were placed and then the protozoa were observed with an increase of 100X and then with 400X. Entamoeba gingivalis could be seen in 20% of the samples, followed by Trichomonas tenax in 4% of those analyzed. Attention was drawn to the presence of Eimeria sp oocysts in 15% of the patients, which is indicative of contamination with feces of domestic animals infected with this coccide (mammals or birds). The presence of gingivitis and caries in all infected patients and the association between these protozoa and dental diseases (indicated by some authors), require the increase of dental hygiene campaigns to eliminate these parasites and end their transmission.